An Intricate Encounter? Cultural Significance and Accessibility in the Conservation of the Nineteenth- and Twentieth Century Monuments of Thessaloniki - Zygomalas, Dimitrios (Protection of Cultural Heritage, 2022)
Located in the north of Greece, the city of Thessaloniki encompasses approximately 320 monuments of the 19th and 20th century. Addressed under Greek law as “modern” monuments, most of them were conserved over the past 40 years, with little if any attention to the issue of adaptation to accessibility needs in the initial conservation works. Nonetheless, in more recent projects, specific care was displayed, largely through interventions aiming to facilitate physical access, with two cases of people with disabilities in mind, namely users of wheelchairs and people with restricted mobility. In each of these interventions, two special issues arise: on one hand, the extent to which the safeguard of cultural significance has placed limits on the pursuit of accessibility, and on the other, the degree to which the initiatives undertaken for accessibility have affected cultural significance. Based on extensive on-site research and genuine evaluation, this paper seeks to provide a complete picture and didactic appraisal of this two-way relation. To this end, it undertakes a thorough analysis and assessment of the interventions completed in the so far three main directions of action for accessibility improvement in the “modern” monuments of Thessaloniki: (1) Establishing an entrance, (2) Providing unobstructed horizontal circulation, and (3) Ensuring smooth vertical movement. This analysis allows for a clear answer to be given to the question posed in the title, in addition to revealing prospects for the enhancement of the encounter of cultural significance and accessibility in the most sizable segment of Thessaloniki’s architectural heritage.